RESPONDING AND ANALYSING: STAGES OF TEACHING FUNCTIONAL GRAMMAR IN INDONESIAN CONTEXT - Bumela, Lala (Universitas Pendidikan Indonesia, 2014)
Abstract: This paper offers an alternative to the teaching of a functional grammar course in Indonesian TEFL tertiary level context. An issue raised here is whether the course should directly require students to undertake textual analysis or provide them first with subjective reading experiences. This issue is inspired by Jones and Lock¹s approach to teaching grammar in context (2011). This paper reports on a study that focused on two related phases of dealing with texts: responding and analyzing. In the first phase, students were encouraged to take a personalised approach in responding to written English texts. They had the freedom to decide whether the texts were meaningful for them in certain ways. Mckee (2003) and Lehtonen (2000) posit that as the sole decision maker in meaning negotiation, readers perceive the meaningfulness of texts in very diverse ways. In the second phase of the study, the students undertook an individual analysis of different text types. This study reveals that a successful textual analysis is determined by how students make sense of the texts. The analysis of context of situation, for example, becomes meaningful to students after they demonstrate a proper position as a reader. This, in turn, helps them in gaining insights into the structure and grammar of those texts. Keywords: systemic functional linguistics, genre-based approach, textual analysis